Cyclones and earthquakes the Jesuits, prediction, trade, and Spanish dominion in Cuba and the Philippines, 1850-1898 - Anduaga Egaña Aitor (Ateneo de Manila Univesity Press, 2017)
This book addresses these issues and shows how the Spanish Jesuits and military engineers sent to these islands became active participants in the development of meteorology and the earth sciences. This book is an original, rigorous, and well-documented study of how two central fields of scientific prevention--cyclone prediction and earthquake-resistant construction--have their roots in the commercial, military, and educational context of late-nineteenth-century Spanish insular possessions. Drawing on a wide variety of archival sources and primary literature, the book shows the complexity and multi-sided nature of modern science, in particular the science of prevention--Provided by publisher.